Pengaruh Pemberian Pakan Beryodium terhadap Pertumbuhan dan Kandungan Yodium Benih Ikan Mas (Cyprinus carpio) [Effect Of Iodized Feeding On The Growth And Content Of Iodine In Carpfish Seed (Cyprinus carpio) ] - Agustono Agustono; Lia Enggar C. W; Mirni Lamid (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Carpfish culure have a quiet effort to profit and developed by people, because it have characteristic like adapted with the environtment, have rapid growth and resistance of disease. Carpfish cultivation is often cultivated in mountainous area far from sources of iodine (Cholik etc, 2002 ; Susanto, 1997). This causes iodine contain is very low, carp fish has only 1.7 mg/100g iodine contain. That amount is not sufficient people nutrition needs. Purpose of this study was to increase the iodine contain and growth. Experiment have been conducted in April until May 2011, for 1 month in Aquaculture Development Laboratory Hang Tuah University, Surabaya. Data retrieval was done by observation, direct participation and documentation thechnique. The research method is an experiment method with a completely randomized desigen consisted of 5 treatment and 4 replication, at a dose of 0 mg / kg of feed, 20 mg / kg of feed, 40 mg / kg of feed, 60 mg / kg feed and 80 mg / kg of feed. Each treatment used 15 carp seed (Cyprinus carpio) measuring 5-8 cm is maintained for 30 days. The parameter used include the primary parameter and parameter support. The main parameter of the growth and content the iodine, while supporting the water quality parameter. Result of this study were analized by using analysis of various with an error rate 5% later, followed by Duncan multiple rate test. Result of this study indicate that feeding iodized can increased the growth in wight and iodine content of carp.